Behavioral ecology of Oriental Magpie Robin Copsychus saularis - Karna, Jyoti (Nepalese Journal of Biosciences, 2013)
Every species of bird possesses some behavior which differ it from other species. It was interesting to note that species wise some different peculiar behaviors are found. Several ornithologists have described about Oriental Magpie Robin (Fleming et al., 1984; Grimmett et al., 2000; Ali, 2002). In case of the Oriental Magpie Robin, behavioral ecology such as feeding behavior, breeding behavior, nesting ecology, territorial behavior, social behavior, communicational behavior and singing behavior were observed and studied in Biratnagar, Nepal for one year.